If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1x + -2)(3x + -5) = (-3x + 1)(x + 3) Reorder the terms: (-2 + -1x)(3x + -5) = (-3x + 1)(x + 3) Reorder the terms: (-2 + -1x)(-5 + 3x) = (-3x + 1)(x + 3) Multiply (-2 + -1x) * (-5 + 3x) (-2(-5 + 3x) + -1x * (-5 + 3x)) = (-3x + 1)(x + 3) ((-5 * -2 + 3x * -2) + -1x * (-5 + 3x)) = (-3x + 1)(x + 3) ((10 + -6x) + -1x * (-5 + 3x)) = (-3x + 1)(x + 3) (10 + -6x + (-5 * -1x + 3x * -1x)) = (-3x + 1)(x + 3) (10 + -6x + (5x + -3x2)) = (-3x + 1)(x + 3) Combine like terms: -6x + 5x = -1x (10 + -1x + -3x2) = (-3x + 1)(x + 3) Reorder the terms: 10 + -1x + -3x2 = (1 + -3x)(x + 3) Reorder the terms: 10 + -1x + -3x2 = (1 + -3x)(3 + x) Multiply (1 + -3x) * (3 + x) 10 + -1x + -3x2 = (1(3 + x) + -3x * (3 + x)) 10 + -1x + -3x2 = ((3 * 1 + x * 1) + -3x * (3 + x)) 10 + -1x + -3x2 = ((3 + 1x) + -3x * (3 + x)) 10 + -1x + -3x2 = (3 + 1x + (3 * -3x + x * -3x)) 10 + -1x + -3x2 = (3 + 1x + (-9x + -3x2)) Combine like terms: 1x + -9x = -8x 10 + -1x + -3x2 = (3 + -8x + -3x2) Add '3x2' to each side of the equation. 10 + -1x + -3x2 + 3x2 = 3 + -8x + -3x2 + 3x2 Combine like terms: -3x2 + 3x2 = 0 10 + -1x + 0 = 3 + -8x + -3x2 + 3x2 10 + -1x = 3 + -8x + -3x2 + 3x2 Combine like terms: -3x2 + 3x2 = 0 10 + -1x = 3 + -8x + 0 10 + -1x = 3 + -8x Solving 10 + -1x = 3 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 10 + -1x + 8x = 3 + -8x + 8x Combine like terms: -1x + 8x = 7x 10 + 7x = 3 + -8x + 8x Combine like terms: -8x + 8x = 0 10 + 7x = 3 + 0 10 + 7x = 3 Add '-10' to each side of the equation. 10 + -10 + 7x = 3 + -10 Combine like terms: 10 + -10 = 0 0 + 7x = 3 + -10 7x = 3 + -10 Combine like terms: 3 + -10 = -7 7x = -7 Divide each side by '7'. x = -1 Simplifying x = -1
| -3x^2+6=1 | | x(5x-4)(x+9)= | | 7.6x-3.2(3.1x-2.4)= | | 2(2x-1)+2x=6(x-1) | | 3x+8x-19=x^2+1 | | -4=-a/5 | | 3(x+1)+4=2(x-1)+x | | .085(5)d-.075(4)d=1250 | | -25=-9x-33+6x-6 | | 6x-4+x=8+x | | 17+n=-2 | | -27=-2x+5x+3 | | 17+n=-21 | | -85=-5 | | -14=3a+6-5a | | t+(-33)=30 | | 7x-4=5x-22 | | x+(-2)=-9 | | -x-(-10x)= | | 7x+9+6x=74 | | 1x+12=-8x+6 | | 4x+15=hx | | 1x+12=8x+6 | | -10=3x+2 | | 7x-2=4x+7x+4 | | n+(-5)=1 | | -x-(10x)= | | 3x-5=-8x-5 | | (2x+4)*(x-3)=(x-1)*(2x-12) | | -4(-6+2t)=-30+t | | (2t+t-6)(2t+2t-1)= | | 120+12(30)+x=900 |